Oxidative Stress and Its Regulation in Diabetic Retinopathy - Cameron D. Haydinger; Genevieve F. Oliver; Liam M. Ashander; Justine R. Smith (MDPI AG, 2023)
Diabetic retinopathy is the retinal disease associated with hyperglycemia in patients who suffer from type 1 or type 2 diabetes. It includes maculopathy, involving the central retina and characterized by ischemia and/or edema, and peripheral retinopathy that progresses to a proliferative stage with neovascularization. Approximately 10% of the global population is estimated to suffer from diabetes, and around one in 5 of these individuals have diabetic retinopathy. One of the major effects of hyperglycemia is oxidative stress, the pathological state in which elevated production of reactive oxygen species damages tissues, cells, and macromolecules. The retina is relatively prone to oxidative stress due to its high metabolic activity. This review provides a summary of the role of oxidative stress in diabetic retinopathy, including a description of the retinal cell players and the molecular mechanisms. It discusses pathological processes, including the formation and effects of advanced glycation end-products, the impact of metabolic memory, and involvements of non-coding RNA. The opportunities for the therapeutic blockade of oxidative stress in diabetic retinopathy are also considered.